The Impact of Ethical Leadership and Employee Engagement on Customers’ Perceived Service Quality: A Study of Sri Lankan Public Service - Achini Tharanga Wijesekera; R. Lalitha S Fernando (Journal of Business & Management, 2023)
This paper investigates how ethical leader influences employee engagement for enhancing the quality of public service in Sri Lanka while examines their customers’ perception of service quality, employees’ perception of the style of ethical leadership, and the level of employee engagement. For that, two questionnaires were distributed. The first questionnaire was distributed through 500 employees in 83 Divisional Secretaries to identify the level of ethical leadership and employee engagement. The second questionnaire was distributed to 2500 customers to identify the level of service quality. To measure these constructs customized scales were used. The results found that, the customers were generally satisfied with the service provided by the public service. Employees in public service were satisfied with the ethical leadership of their administrators and they engage well. The results indicate that ethical leadership and employee engagement significantly affect customers’ perceived service quality and employee engagement is partially mediates the association between ethical leadership and service quality. This study helps to identify the extent of ethical leadership exhibited by public officers, and how it influences service quality through employee engagement. The findings will help the public service to identify its strengths and weaknesses, and will serve as an important source of feedback to the public service that can be used in decision-making processes to better serve customers. In addition, this paper filled the gap in the literature by addressing the relationship between ethical leadership, employee engagement and customers’ perceived service quality. The empirical findings of this will help to enhance the body of knowledge in the area of service quality. The findings will help to uncover the nature of ethical leadership, and employee engagement in the existing public service in Sri Lanka